Extremism, knowledge, and overconfidence in the covid-19 restriction times - Hatori, Tsuyoshi; Bhandary, Netra Prakash (Frontiers in Psychology, 2024)
Public response to restriction policy against the novel coronavirus disease (COVID-19) can polarize into two extremes: one absolutely in favor of restrictions for the sake of human life and health, and other absolutely against the restrictions for the sake of human rights and daily life. This study examines psychological nature of extremism regarding individuals' self-restraint from social behavior, which was and has been encouraged by the Japanese government as restriction measures, as well as possible measures to mitigate this extremism. We hypothesize that people with more extreme views on self-restraint tend to have less knowledge of this virus, and, nevertheless, tend to be more overconfident in the sense that they falsely believe they understand COVID-19 and the effects of self-restraint. It is also postulated that overconfidence can be reduced by asking them to explain how self-restraint works. To test these hypotheses, we conducted an online experiment on the Japanese adults (n = 500) to measure the extent of their knowledge of COVID-19 and to examine the effect of explanation task on their understanding regarding COVID-19 and extremism. The results indicate that the extreme attitudes were associated with insufficient knowledge about the symptoms, risks, and characteristics of COVID-19. Moreover, their extreme attitudes tended to moderate through this experimental study to an extent that they realized they did not understand COVID-19 including the effects of self-restraint. This suggests that people with extremism may have been overconfident in their own understanding of the COVID-19 restrictions.